First stars and reionization: Spinstars. Issue 6 (1st July 2013) - Chiappini, C.
Abstract: Soon after the Big Bang, the appearance of the first stellar generations (hereafter, first stars) drastically changed the course of the history of the Universe by enriching the primordial gas with elements heavier than helium (referred to as metals) through both stellar winds and supernova explosions. High‐resolution hydrodynamical simulations of the formation of the first stars suggest these objects to have formed in dark matter mini‐halos, and to have played a key role in the formation of the first galaxies. Today these stars are (most likely) long dead, and even though next generation facilities will push the observational frontier to extremely high redshifts, with the aim of discovering the first galaxies, the first stars will still lie beyond reach. Thus, the only way to constrain our theoretical understanding of the formation of the first stars is to search for their imprints left in the oldest, still surviving, stars in our own backyard: the Milky Way and its satellites. Which imprints are we looking for, and where can we find them? We address these questions in the present review. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)